2020
DOI: 10.1097/ccm.0000000000004071
|View full text |Cite
|
Sign up to set email alerts
|

Online Learning and Residents’ Acquisition of Mechanical Ventilation Knowledge: Sequencing Matters

Abstract: Objective: Rapid advancements in medicine and changing standards in medical education require new, efficient educational strategies. We investigated whether an online intervention could increase residents’ knowledge and improve knowledge retention in mechanical ventilation when compared with a clinical rotation and whether the timing of intervention had an impact on overall knowledge gains. Design: A prospective, interventional crossover study conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Unlike face-to-face simulation, online education has the potential of reaching a massive number of learners. A recent study conducted on American residents rotating in Pediatric ICU showed that an online virtual mechanical ventilation simulator increased resident’s knowledge on this topic [ 24 ]. With short rotation periods, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike face-to-face simulation, online education has the potential of reaching a massive number of learners. A recent study conducted on American residents rotating in Pediatric ICU showed that an online virtual mechanical ventilation simulator increased resident’s knowledge on this topic [ 24 ]. With short rotation periods, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…No virtual or augmented reality interventions for healthcare professional education in pediatric intensive care were identified through this review. Three studies ( 9 , 12 , 13 ) included interventions aimed at residents rotating in the PICU, two studies ( 14 , 15 ) included interventions aimed at nurses, two studies ( 11 , 16 ) included interventions aimed at a multidisciplinary healthcare professionals, and one study ( 10 ) included an intervention aimed at transport nurses and paramedics. In terms of outcome measures analysed, the majority (6 of 8) of studies utilized participant surveys to assess satisfaction or change in attitudes ( 9 11 , 14 16 ), and nearly half (4 of 8) included pre- and post-intervention multiple-choice question tests ( 9 , 10 , 12 , 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decade, opportunities to share PCC educational materials and global health educational materials online have increased dramatically, again with rapid advancement during the COVID-19 pandemic. Some schools have created entire online PICU curricula ( 70 ), while others have utilized online education to augment PICU residents' understanding of certain topics (e.g., mechanical ventilation) ( 71 ). Others created online global health educational resources designed to be widely shared and used in various settings.…”
Section: Virtual Technology Collaboration and Resource Sharingmentioning
confidence: 99%